Partially connnected steel-concrete composite plate girders - Mohd Yazmil Md Yatim; Nandivaram E.Shanmugam; Wan Hamidon Wan Badaruzzaman (Fakulti Kejuruteraan ,UKM,Bangi., 2011)
A method to predict the bending behavior and load carrying capacity of steel-concrete composite plate girders with partial shear connection under different load condition is presented. Based on curvature compatibility principle, the analytical solutions were performed by incorporating the degree of coposite interaction and post-buckling strength. It is observed that the bending stiffness and ultimate load drops accordingly with decreasing degree of interaction. Accuracy of the proposed method is assesed by comparing the results with corresponding non-linear finite element analysis using LUSAS software. A satisfactorily correlation between the results has been observed.